2011
DOI: 10.1353/foc.2011.0005
|View full text |Cite
|
Sign up to set email alerts
|

Early Care and Education for Children in Immigrant Families

Abstract: A substantial and growing share of the population, immigrant children are more likely than children with native-born parents to face a variety of circumstances, such as low family income, low parental education, and language barriers that place them at risk of developmental delay and poor academic performance once they enter school. Lynn Karoly and Gabriella Gonzalez examine the current role of and future potential for early care and education (ECE) programs in promoting healthy development for immigrant child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(95 citation statements)
references
References 45 publications
2
87
1
5
Order By: Relevance
“…Multiple authors argue that driver's licenses enable unauthorized immigrants to contribute to the local economy, with positive externalities for the community as a whole (9,30). For instance, workers with a car are found to have higher earnings (10), and driver's licenses give unauthorized immigrants access to a larger number of services, such as financial (8), health (31), or education services (32). Similarly, one study has found correlational evidence that immigrants without any form of identification have considerably less political knowledge than naturalized citizens or immigrants with a driver's license, other government picture identification, or green card (33).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple authors argue that driver's licenses enable unauthorized immigrants to contribute to the local economy, with positive externalities for the community as a whole (9,30). For instance, workers with a car are found to have higher earnings (10), and driver's licenses give unauthorized immigrants access to a larger number of services, such as financial (8), health (31), or education services (32). Similarly, one study has found correlational evidence that immigrants without any form of identification have considerably less political knowledge than naturalized citizens or immigrants with a driver's license, other government picture identification, or green card (33).…”
Section: Resultsmentioning
confidence: 99%
“…Studies show that children of immigrants traditionally have lower rates of nonparental care than do children of native parents (Karoly & Gonzalez, 2011), but knowledge concerning what drives such differences is limited. Few studies have carefully examined whether predictors of child care, especially for infants and toddlers, operate similarly in immigrant families as in native families.…”
Section: Patterns Of Infant and Toddler Ece Use In Immigrant Familiesmentioning
confidence: 99%
“…With respect to infant and toddler ECE in particular, Urban Institute's National Survey of America's Families showed that children of immigrants under the age of three were 1.5 times more likely than children in native families to be cared for by their parents as opposed in ECE settings (Matthews & Ewen, 2006). Two recent studies using NHES data found that children of immigrants aged 0-2 were less likely to experience ECE compared to children with native parents even after controlling for basic sociodemographic factors (Greenberg & Kahn, 2011;Karoly & Gonzalez, 2011). Evidence regarding whether differences exist in immigrant families' use of specific types of early nonparental care is less clear.…”
Section: Ece Selection In Immigrant Familiesmentioning
confidence: 99%
“…De igual manera lo reportado por Restrepo, et al (25) indica que la educación materna influye de mayor manera y más fuerte el desarrollo del lenguaje de los niños que su condición socioeconómica. Dicha influencia del nivel de educación materno está presente en los diferentes grupos raciales, étnicos o contextos rurales y urbanos (27).…”
Section: Maltrato Infantilunclassified